An Empirical Study of Integrating Orff-Schulwerk in Music Classes to Improve College Students’ Social Competence in the Post Epidemic Era - Cai, Zhining; Daoruang, Krisada; Posrithong, Arethit (Journal of Ecohumanism, 2024)
As the global epidemic eases, college students face increasing Social-Skills problems, especially when Social-Skills are reduced due to prolonged home isolation. This study investigated the effectiveness of Orff-Schulwerk in enhancing the Social-Skills of college students. Taking students of Z College School in Southern China as the research object, the current social status and needs of college students were analyzed through questionnaires and in-depth interviews. The findings suggest that Orff-Schulwerk significantly improves students’ Social-Skills through its unique collective participation and creative expression, especially in enhancing teamwork, communication skills and self-confidence. This study not only provides new perspectives on the application of music education in higher education, but also provides empirical support on how to promote the development of college students’ Social-Skills through art education in the post epidemic era.